Protein biomarkers for bipolar II disorder are correlated with affective cognitive performance - Sheng-Yu Lee; Sung-Chou Li; Tzu-Yun Wang; Ru-Band Lu; Liang-Jen Wang; Kuo-Wang Tsai (BMC Psychiatry)
Abstract Background In our previous research, we identified five candidate proteins—Carbonic Anhydrase 1 (CA-1), Matrix Metallopeptidase 9 (MMP9), Peroxiredoxin 2 (PRDX2), Phenylalanyl-tRNA Synthetase Subunit Beta (FARSB), and Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9)—as prospective biomarkers for bipolar II disorder (BD-II). In this study, we explored the relationships between these potential plasma proteins and cognitive performance in BD-II patients using the Brief Assessment of Cognition in Affective Disorders (BACA), a validated tool for assessing cognitive deficits in mood disorders. Methods One hundred and seventeen participants with BD-II and 41 controls participated in this study. Plasma concentrations of the aforementioned proteins were measured, and cognitive performance was evaluated using the BACA. Results Our findings indicated that the BD-II group scored significantly lower than the control group across several BACA subtests, including Digit Sequencing, Symbol Coding, Verbal Memory, and Verbal Fluency, and in overall composite scores and all subtests of the Affective Interference Test (AIT) and Emotion Inhibition Test (EIT). Notably, we observed significant correlations in the BD-II group between levels of CA-1 (r = -0.26, P = 0.005), FARSB (r = 0.399, P < 0.001), and MMP9 (r = 0.24, P = 0.008) with the AIT-Cued affective words subtest. In contrast, a significant correlation was found between the Symbol Coding task and PCSK9 levels (r = 0.35, P = 0.003) in the control group, but not in the BD-II group. Conclusion These findings offer new perspectives on the underlying mechanisms contributing to cognitive decline in individuals with BD-II.